Sustainability driven multi-criteria project portfolio selection under uncertain decision-making environment. (February 2020) - Ma, Junfeng; Harstvedt, James D.; Jaradat, Raed; Smith, Brian
Highlights: Sustainable project portfolio selection needs to include full-dimension sustainability. Fuzzy logic is able to support decision-making under uncertainty in project portfolio selection. TOPSIS approach can handle several conflict attributes simultaneously in project portfolio selection. Abstract: As competition in the global market has increased over the past decades, new projects are setting the foundation for organizational success. Effective project selection is becoming more complicated to implement; new measures of performance must be examined and integrated into projects to ensure their successful completion. One solution to this problem is the implementation of Project Portfolio Selection (PPS). PPS involves the utilization of Key Performance Indicators (KPI) in combining multi-criteria decision-making methods to analyze and compare the potential success of different projects regarding various dimensions of an organization. Among these KPI, sustainability becomes increasingly important and attracts more attention in society. This study adopts a three-pillar concept: economic, environmental, and social sustainability to investigate and measure sustainability. The main purpose of this study is to target project selection from the perspective of sustainability in an uncertain decision-making environment. To achieve this purpose, a fuzzy logic model based on the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) approach is used to incorporate sustainability under uncertainty to obtain the most sustainable solution. A large-scale paper manufacturing company case study is presented to demonstrate the applications.